Review of: iBioSeminars and iBioMagazineReview of: iBioSeminars (http://ibioseminars.org/) and iBio-Magazine (http://ibiomagazine.org/). - Pamela A. Marshall (American Society for Microbiology, 2013)
Review of: iBioSeminars (http://ibioseminars.org/) and iBio-Magazine (http://ibiomagazine.org/).